Using the dehisced surgical wounds aetiology-specific T.I.M.E. clinical decision support tool to promote consistent holistic wound management and eliminate variation in practice. Issue 4 (2021) - Phelps, Stacy; Smith, Wanda; Smith, Tesha; Benton, Beth; Rybolt, Mallory; White, Taylor; Edwards, Melanie
No abstract available